Information Digitalization and Socialization of the Savings and Loan Video at the “Usaha Wanita Mandiri” Women’s Cooperative - Mariana Rista Ananda Siregar; Qoute Nuraini Cahyaningrum (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The women’s cooperative “Usaha Wanita Mandiri” was established as a forum for women to be economically empowered. However, in the enforcement of rules of savings and loan activities, the management often encounters problems with loan repayments in each installment period. This program aimed to educate supervisors, administrators, and coordinators in charge of the Kopwan Utama group regarding the importance of keeping regulatory archives in the form of digital videos and facilitating the dissemination of information on savings and loan regulations that are still in paper form. The community service program consists of focus group discussions and video socialization. The formulation of regulations and the video socialization were conducted face-toface and through online communication platforms, such as whatsapp and youtube. Because of the pandemic, issues arose during the focus group discussions and socialization, wherein some stages were not attended by all participants. The dissemination of the video via whatsapp and youtube is acknowledged by the supervisors, administrators, and coordinators of the groups to help provide their members with videos on savings and loans.